Firestarters: Sparking a Constellation of Change in Recognition, Badging, and Microcredentials (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
ePIC2025 provided an annual global engagement of experts around recognition, badging, and to a lesser extent, microcredentials. In 2025 we endeavored to activate a coordinated engagement in the British Columbia, Canada post-secondary sector that brought together higher education, industry, and provincial government for a 1.5-day event entitled CredX. We heard from local, national, and international experts on a variety of topics related to how we can better foster and recognize skills, as well as how we can leverage improved systems to better see the individual and help improve livelihoods in our region. This presentation provides an overview of what we learned, what worked and stuck, what didn't work, and where things have evolved since the event took place in late February 2025. We concluded with recommendations for anyone considering a similar approach. British Columbia is a sector comprised of 25 public universities, colleges, and institutes of higher education. Microcredentials are an active initiative of the Ministry of Post Secondary Education and Future Skills, but they have been largely divorced from conversations of the recognition of prior learning (PLAR) and badges. As we outlined in our presentation at the 2024 ePIC conference, we saw the need and urgency of bringing together government, industry, and higher education stakeholders to hear from and engage with subject matter experts from a variety of jurisdictions who could speak to the importance of considering all of these components, along with microcredential initiatives. Through the valuable connections we made at ePIC, we were able to invite several conference alumni to present on some of the important topics that have been presented at ePIC over the last few years. Although CredX could not include all topics, perspectives, and speakers that ought to be included, it was designed to be more than just a traditional conference by consciously centering diverse voices, perspectives, and ideas. We invited participants to connect ideas into new constellations of a better future for our province and our communities. We concluded our symposium with a session in which everyone worked together in groups to identify, distill, and prioritize the essential needs, ideas, and opportunities that were generated throughout the symposium. Those identified priorities would then serve as a launch point for subsequent tangible actions that would shift these ideas into a functional and accessible reality within the sector. Per its stated objectives, the symposium was quite successful. The topics were curated and scaffolded to establish a shared understanding of the concepts in question and provide ample opportunity to engage in the conversations by learning from diverse experts and perspectives represented within the room.  The presentations helped broaden the group's understanding and appreciation of similar efforts and initiatives elsewhere in the world, and discussions focused on applying that learning to envision something better for B.C.  While the experience at the symposium itself achieved our objectives, it has proven difficult to effectively move those priorities into action at scale. It has proven difficult to shepherd strong ideas into action. Most notably, we operate within siloed institutions that prioritize our respective aims and priorities, making it difficult to shepherd strong ideas into action. Nevertheless, we have made some progress toward improving how our region can better understand and leverage microcredentials, badges, and recognition practices, most significantly in challenging cultural inertia. The acts of stepping forward, of making space for needed conversations, of intentionally fostering shared interests in a format that leverages the shared frustrations and zeal for realizing change within the sector, of doing the work of firestarters to spark inquiry and engagement in these topics across our region—these are some of the needed components upon which we can build sustainable momentum in the months and years ahead. Creating CredX provided our province with the collaborative focus to make changes for the better with a common understanding of what we need to pursue and why. Our efforts now turn to exactly how that work will continue year over year, and how we both individually and collectively invest ourselves into the work of progressing these shared aims even further. Keywords: shaping culture, transformation, system change, recognition